Speech Act Used by Main Character “Teddy” in The Man from Toronto Movie - Trio Setia Estrada; Endratno Pilih Swasono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The purpose of this study is to describe the speech act of the main character "Teddy" in The Man from Toronto Movie. The other description of this study is to find the speech acts function in Teddy's utterances. This study used a qualitative method to acquire the data. The writers collected the data by downloading the transcript of The Man from Toronto Movie. In investigating the speech acts of Teddy, this study applied Searle's (1980) theory of speech acts in analyzing the utterances produced by Teddy in The Man from Toronto Movie. The results showed that Teddy's 177 utterances were representative, expressive with 118 utterances, directive with 111 utterances, commissive with 10 utterances, and declarative with 2 utterances.